2009
DOI: 10.1007/s10886-008-9587-z
|View full text |Cite
|
Sign up to set email alerts
|

Is (−)-Catechin a Novel Weapon of Spotted Knapweed (Centaurea stoebe)?

Abstract: The novel weapons hypothesis states that some invasive weed species owe part of their success as invaders to allelopathy mediated by allelochemicals that are new to the native species. Presumably, no resistance has evolved among the native species to this new allelochemical (i.e., the novel weapon). In their native habitat, however, the plants that co-evolved with these invasive species have theoretically evolved defenses that obviate the allelochemical advantage. Previous studies have claimed that catechin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 65 publications
(36 reference statements)
4
64
0
1
Order By: Relevance
“…Other papers provide rigorous evidence that the claims of strong phytotoxicity of (-)-catechin in either an aqueous medium or soil are unfounded. 19,20 Our most recent paper 20 strongly supports the view that neither enantiomer of catechin is likely to be involved in allelopathy of any species and questions whether (-)-catechin could act as a toxin through generation of oxidative stress, as claimed by Bais et al 12 We found (-) and (+)-catechin to have similar, weak phytotoxicities, with little or no phytotoxicity in soils at concentrations far exceeding those reported in any of the above papers. Furthermore, we confirmed that it is a strong antioxidant, virtually ruling out that it could harm plants by causing oxidative stress.…”
Section: Proving Allelopathysupporting
confidence: 57%
See 3 more Smart Citations
“…Other papers provide rigorous evidence that the claims of strong phytotoxicity of (-)-catechin in either an aqueous medium or soil are unfounded. 19,20 Our most recent paper 20 strongly supports the view that neither enantiomer of catechin is likely to be involved in allelopathy of any species and questions whether (-)-catechin could act as a toxin through generation of oxidative stress, as claimed by Bais et al 12 We found (-) and (+)-catechin to have similar, weak phytotoxicities, with little or no phytotoxicity in soils at concentrations far exceeding those reported in any of the above papers. Furthermore, we confirmed that it is a strong antioxidant, virtually ruling out that it could harm plants by causing oxidative stress.…”
Section: Proving Allelopathysupporting
confidence: 57%
“…One could hypothesize that catechin is only substantially active when in the presence of some other component of C. stoebe. However, dramatic synergism between any allelochemicals has thus far not been rigorously proven (discussed by Duke et al 20 ). The half-life of catechin in soil is increased by the presence of other phenolic compounds, but it is still short and essentially inactive.…”
Section: Proving Allelopathymentioning
confidence: 99%
See 2 more Smart Citations
“…Some compounds that are quite active in soil-free bioassays such as those discussed above are virtually or completely inactive in soil (e.g., Duke et al 2009;Hiradate et al 2010). Activity of a compound can also vary considerably between different soil types (Hiradate et al 2010).…”
Section: Pitfallmentioning
confidence: 99%